Bacteriological Profile of Wound Swab and Their Antimicrobial Susceptibility Pattern in Shaheed Suhrawardy Medical College, Dhaka - Tarana, Mst Naznin; Fardows, Jannatul; Farhana, Nasreen; Khatun, Rehana; Akter, Shahida (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: Wound infections are global problem in the field of surgery associated with long hospital stay, higher treatment expenditure, morbidity and mortality. Objective: To isolate and identify the bacteria causing wound infection and to determine the antimicrobial susceptibility pattern. Methods: This retrospective study was conducted in the Department of Microbiology at Shaheed Suhrawady Medical College, Dhaka from January 2017 to December 2017 for a period of one (01) year. A total of 190 wound swabs were collected from the patients who were visited in outpatient department and were admitted at inpatient department with skin and soft tissue infection. Swabs from the wound were inoculated on appropriate media and cultured and the isolates were identified by standard procedures as needed. Antimicrobial susceptibility testing was done by disc diffusion method according to ‘The Clinical Laboratory Standard Institute’ guidelines. Results: In this study, out of 190 cases 115 (60.52%) were male and 75 (39.47%) were female and majority 85(44.73%) were in the age group of 16 to 30 years. A total number of 190 isolates were obtained, among which 124 (65.25%) were culture positive cases. Among the isolated organisms predominant bacteria was Staphylococcus aureus 68 (35.79%) followed by Escherichia coli 30 (15.79%), Pseudomonas 14 (7.37%), Klebsiella 6 (3.16%), Proteus 4 (2.10%) and Acinetobacter 2 (1.05%). Staphylococcus aureus was sensitive to linezolid (94.11%), vancomycin (88.23%) and amikacin (70.58%). Among the Gram negative isolates Escherichia coli was predominant and showed sensitivity to imipenem (80%), amikacin (70%), ceftazidime (60%), piperacillin+ tazobactum (56.66%), colistin (53.33%). Pseudomonas showed sensitivity to colistin (78.57%), imipenem (71.42%). Klebsiella showed sensitivity to imipenem (83.33%), amikacin (66.66%), piperacillin+ tazobactum (66.66%), and colistin(66.66%). Conclusion: Staphylococcus aureus was the most frequently isolated pathogen from wound swab and the antibiotic sensitivity pattern of various isolates will guide for appropriate selection of antibiotics against wound infection, so as to reduce the spread of resistant bacteria. J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 65-68